2016
DOI: 10.1515/pjct-2016-0004
|View full text |Cite
|
Sign up to set email alerts
|

Application of pyrolysis process in processing of mixed food wastes

Abstract: The food industry produces large amounts of solid and also liquid wastes. Different waste materials and their mixtures were pyrolysed in the laboratory pyrolysis unit to a fi nal temperature of 800°C with a 10 minute delay at the fi nal temperature. After the pyrolysis process of the selected wastes a mass balance of the resulting products, off-line analysis of the pyrolysis gas and evaluation of solid and liquid products were carried out. The highest concentration of methane, hydrogen and carbon monoxide were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Grycová et al [25] report a study on the conversion of food wastes into energy using pyrolysis process. Coker [26] reports a study on conversion of food waste into biogas energy and fertilizer using an anaerobic digestion.…”
Section: Waste Generation In the United Arab Emirates (Uae)mentioning
confidence: 99%
“…Grycová et al [25] report a study on the conversion of food wastes into energy using pyrolysis process. Coker [26] reports a study on conversion of food waste into biogas energy and fertilizer using an anaerobic digestion.…”
Section: Waste Generation In the United Arab Emirates (Uae)mentioning
confidence: 99%
“…It could be originated from the agricultural waste such as wood, rice husks, oil palm shells, cocoa pod husks and other wastes. (Grycová et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…More economical and environmentally friendly is to use waste material 5, 76, 77 . To date, it has been reported that activated carbons have been prepared from agricultural residues such as sawdust 76 , coconut shell 78 , olive stone 79 , beet molasses 12 , fungi 80 , corn syrup 76, 81 , kraft lignin 82 , ebony wood 83, 84 , mahogany wood 82 and food waste 85,86 .…”
Section: Introductionmentioning
confidence: 99%